PENGEMBANGAN MEDIA PEMBELAJARAN BERBASIS ANDROID SEBAGAI PENDUKUNG PEMBELAJARAN MATA KULIAH BELAJAR DAN PEMBELAJARAN - Subiyantoro, Singgih; Nugroho, Anwari Adi (IPTPI Surakarta, 2018)
This article aims to explain an android-based instructional media development procedure to enhance teaching and learning. At present we have entered a new era that demands technological literacy and data literacy, namely the big data era. People also call it an era of disruption 4.0. Some characteristics of this era are big volume, variety, velocity, veracity, and transitory. The ease of access to information brings benefits as well as various risks. Media development procedures can refer to development models that have been created by experts. One model that can be used is the ADDIE (Analiyz, Design, Development, Implementation and Evaluation) model. Regarding the procedures of developing android-based instructional media will be explained further in Chapter III. The discussion, conclusions, and recommendations contained in this article can be used as consideration for developing or using android-based instructional media, both at school and in college.